Telemedicine and Its Scope in COVID-19: Commentary - Pareek, Kanupriya (Homœopathic Links, 2020)
Telemedicine is a new concept that is developing with a lightning speed in developed countries. The practitioners of medicine are also using this as it has been legalised in many countries.In the coronavirus disease 2019 (COVID-19) times, when the buzzword is physical distancing, telemedicine assumes more importance. People are using this because of its easy availability, which cuts down their waiting time in the hospitals, it is easily accessible and is cost-effective. This is not only used by the modern science but also by the alternative systems of medicine like Ayurveda and Homoeopathy, as well as by the nutritionists, physiotherapists, yoga experts and so many others who are following these audio-visual and telecommunication techniques. It has worked well to reach out to the patients and resolve their queries. It is easy to reach to so many persons via a single platform and guide them. We are here to share some of our views on telemedicine and on the approach adopted by the people across the world, and discuss how it will be implemented by the future generation for the benefits of their lives and the society.
Keywords: telemedicine; telehealth; medical science; telecommunication; cost-effective